EXPERIMENTAL GENETIC RECOMBINATION IN VIVO BETWEEN ESCHERICHIA COLI AND SALMONELLA TYPHIMURIUM - Schneider, H. (The Rockefeller University Press, 1961)
Antibiotic-pretreated mice were fed orally an Hfr culture of streptomycin-resistant E. coli and 1 day later, a streptomycin-resistant F(-) S. typhimurium culture. Hybrids were recovered in relatively small numbers from the feces of these mice within 24 hours demonstrating that genetic recombination can occur within the intestinal tract of a mammalian host under experimental conditions. These hybrids multiplied rapidly and persisted throughout the course of the experiment. In addition, hybrids were recovered which had not been observed in single matings performed in vitro.